PENGARUH KEMAMPUAN MATEMATIK TERHADAP PRESTASI BELAJAR KIMIA - Krisna Merdekawati (UII, 2013)
This study was aimed to investigate the effect of mathematics ability on students’ achievement in chemistry and descriptive howmathematics ability could influence students’ achievement in chemistry. This study used description method. The population in the first study was XIIth grade students senior high school in Magelang, academic year 2012/2013. Samples was taken using cluster randomsampling technique. The data was collected by test method. Independent t-test statistic tool was used to analyze the data collected. Theresult of the test indicated that mathematical ability have significant effect onstudents’ achievement in chemistry. In second study, 30 chemistry teacher was respondent. The result of second study indicated that mathematics ability could influence students’ achievement in chemistry because ofthe teacherswere not noticed students’ mathematics ability.Keywords: mathematics ability, students’ achievement in chemistry